Expression of the apoptosis gene reaper in homeotic, segmentation and other mutants in Drosophila - Zhai, Zongzhao; Stein, Sokrates; Lohmann, Ingrid (Gene expression patterns, 2009)
Apoptosis is an essential process required for development and morphogenesis in metazoan organisms. The apoptosis pathway and cell death machinery have been extensively studied, but little is known how apoptosis genes are regulated in the course of development. In this study, we analyzed the transcriptional regulation of the pro-apoptotic gene reaper (rpr) by performing whole-mount in situ hybridization in embryos mutant for a number of transcription factor genes in Drosophila melanogaster. In sum, our data show that all factors studied have very specific temporal and spatial effects on rpr transcription. Thus, our results reinforce the concept that apoptosis is an essential process for morphogenesis and that apoptosis related genes are under very tight developmental control. In addition, our findings could prove very useful in understanding the function of the factors identified in sculpting the morphology of various embryonic structures by modulating the apoptosis pathway.